2021
DOI: 10.1111/vco.12793
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy reduces the risk of tumour development and influences the histologic continuum in canine mammary tumours

Abstract: Influence of neutering on canine mammary tumorigenesis has been a source of vivid discussion over the last decades. The purpose of this retrospective study was to describe the association between neuter status, tumour size and degree of malignancy in a large population of 625 female dogs with altogether 1459 removed mammary tumours (MTs). MT‐bearing dogs were predominantly intact (80.3%) and intact dogs were overrepresented in the tumour population compared to the control group of >19 000 females (p < .0001). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…Routine OH is often performed because of its protective value against reproductive tract disorders and CMTs. Depending on the age of the dog at the time of OH, potentially fatal CMTs may be preventable 14 , 17 , 18 . However, some studies did not confirm such a beneficial effect 15 , 66 , 67 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Routine OH is often performed because of its protective value against reproductive tract disorders and CMTs. Depending on the age of the dog at the time of OH, potentially fatal CMTs may be preventable 14 , 17 , 18 . However, some studies did not confirm such a beneficial effect 15 , 66 , 67 .…”
Section: Discussionmentioning
confidence: 99%
“…), also considering the adverse effects of early OH 15 17 . Moreover, a recent study suggests that OH performed in adulthood (≥ 4 years of age) may still decrease the risk of CMT development; however, a reduction in the prevalence of benign tumours has been observed in neutered dogs 18 . Even late-spayed dogs (after 2 years of age) had a fourfold lower risk of CMT-related death compared with intact dogs 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these regions, preventive neutering is not a common procedure in dogs [ 6 ]. Currently, it is known that ovariohysterectomy significantly reduces the risk of cancer development [ 8 ].…”
Section: Canine Mammary Tumorsmentioning
confidence: 99%
“…Other risk factors, such as neuter status, time of neutering and breed, were also identified, 6 with entire bitches, bitches of an advanced age (i.e., greater than 12 years) at neutering and breeds such as Boston Terrier, Cocker Spaniel, English Springer Spaniel, German Shorthaired Pointer, Labrador Retriever, Dachshund and Poodle showing increased risk of mammary tumours 7–11 . More recently, it has been reported that early ovariohysterectomy had a protective effect against mammary tumours 12 . However, there remains limited current evidence directly relevant to UK bitches.…”
Section: Introductionmentioning
confidence: 99%